2018
DOI: 10.1371/journal.pone.0204237
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status and health-related behavior with elderly health in China

Abstract: Previous health studies have focused on the correlation between socioeconomic status (SES) and health. We pooled data from the Chinese Longitudinal Healthy Longevity Survey (N = 9765) conducted in 2011, and examined the association of SES and health-related behavior with elderly health in China. The cumulative health disadvantage of the elderly caused by SES can be relieved by lifelong health-related behavior. In the same SES, the odds of self-rated health (SRH) as “good,” mini-mental state examination (MMSE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 48 publications
2
21
0
1
Order By: Relevance
“…Physical activity included activities of daily living (ADL) with six daily activities of eating, dressing, transferring, using the toilet, bathing, and continence. Physical activity was converted into one health variable, namely, impaired physical activity (yes or no), based on the previous measurement methods (Wang et al, 2018;Zaninotto et al, 2018).…”
Section: Physical Activitymentioning
confidence: 99%
“…Physical activity included activities of daily living (ADL) with six daily activities of eating, dressing, transferring, using the toilet, bathing, and continence. Physical activity was converted into one health variable, namely, impaired physical activity (yes or no), based on the previous measurement methods (Wang et al, 2018;Zaninotto et al, 2018).…”
Section: Physical Activitymentioning
confidence: 99%
“…In addition, socioeconomic status (SES) is widely considered to associate with individuals' behavior and health [21][22][23][24]. Wang et al [25] mentioned that healthrelated behaviors could mediate the relationship between SES and elderly health. The relationship between SES and different health-related behaviors are different.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of socioeconomic status (SES) on individual health and health risk behavior has been widely reported [31][32][33][34][35]. A recent study based on Chinese elderly population demonstrated that the health disadvantage caused by SES can be mediated by health-related behavior, and the cumulative health disadvantage could be relieved by lifelong health-related behaviors [32].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of socioeconomic status (SES) on individual health and health risk behavior has been widely reported [31][32][33][34][35]. A recent study based on Chinese elderly population demonstrated that the health disadvantage caused by SES can be mediated by health-related behavior, and the cumulative health disadvantage could be relieved by lifelong health-related behaviors [32]. SES demonstrated quite different associations with various health risk behaviors, low SES population, such as rural elderly, are more likely to report physical inactivity due to poor access to sports resources, but they are less likely to suffer overweight or obesity due to their living and working conditions.…”
Section: Introductionmentioning
confidence: 99%